Analysis of sFas IL-6 levels in thyroid-associated ophthalmopathy: Pre- or poststeroid pulse treatment - Kimihito Maeda (Dove Medical Press, 2008)
Kimihito Maeda, Yuichiro Ohara, Masato Hashimoto, Hiroshi OhguroDepartment of Ophthalmology, Sapporo Medical University, School of Medicine, Sapporo, JapanPurpose: To investigate whether serum levels of soluble Fas (sFas) and interleukin-6 (IL-6) could function as an index of the efficacy of steroid pulse treatment, we examined the serum level of these proteins before and after steroid pulse treatment in thyroid-associated ophthalmopathy patients.Methods: We gathered the blood of thyroid-associated ophthalmopathy patients before or after steroid pulse treatment, obtained serum with a centrifuge, and measured the serum levels of sFas and IL-6 by enzyme-linked immunosorbent assay (ELISA).Results: There was no difference in serum IL-6 value between pre- and poststeroid pulse treatment. Serum sFas value was significantly decreased in both pre- and poststeroid pulse treatment. Furthermore, there was a recognizable improvement in the degree of the extraocular muscle thickening after treatment in cases in whom the serum sFas value was lower than 3 ng/ml prior to the beginning of the therapy. In patients who had a serum sFas value of more than 3 ng/ml, there was no improvement in the degree of thickening of the extraocular muscle.Conclusions: Serum level of sFas is an accurate index of the outcome of steroid pulse treatment in thyroid-associated ophthalmopathy and may become a useful index to gauge the status of convalescence.Keywords: sFas, IL-6, ELISA, thyroid associated ophthalmopathy, steroid pulse treatment